Palliative Care Needs of Children with Cancer and Their Families as Perceived by Family Caregivers - Thamanee, Gewadee; Patoomwan, Autchareeya; Phengjard, Johnphajong (Nursing Research and Innovation Journal, 2019)
Abstract This qualitative descriptive research aimed to study palliative care of children with cancer and their families as perceived by family caregivers. The participants were 15 family caregivers of children who died from cancer and had received treatment and palliative care at Ramathibodi Hospital. Data on palliative care needs of the children with cancer and their families were collected by interview and were analyzed by content analysis. The findings of this study revealed that palliative care needs of the children and their families could be divided into 6 aspects: Treatment information; caring for illness of children; psychological care; spiritual care and end-of-life care; support for caring and bereavement care.Understanding this study could enable the nurses and health providers to evaluate and give palliative care that meets the requirements of children and their families and used to better their quality of life at the end of life.